Moodle-based Harmonization Learning Materials Development: Improving Learning Outcomes Office Management Automation Skills - Muhammad Yusuf; Thamrin Thamrin; Saidun Hutasuhut (RIRAI Publisher, 2024)
The qualification of the teaching material coordination developed using Moodle media and the effectiveness of the materials developed to improve student learning outcomes. This research is developmental research. The development model used in this research is the ADDIE model. The data in this study are data on the validity of teaching materials that have been validated by material experts, media experts, and learning designers. The data collected are further analyzed descriptively to find out the effectiveness of the educational materials developed and to know the efficacy of the teaching materials tested. The results of the research show that Moodle-based coordination materials are worthy of being used to improve the learning outcomes of alignment subjects among students in the X class of OTKP Vocational Education at Swasta Bina Satria Medan. On the results of the post-test, there was an increase in the student's learning outcome by 0.033 (0.3 < g ≤ 0.7) with a moderate criterion. Furthermore, Moodle-based coordination teaching materials are effective in improving the learning outcomes of student coordination subjects. Based on the t test, the magnitude of the thitung value is 2,187, while the ttable value is 0,396. This means that the value of thitung > ttable (2,187 > 0,396), so the teaching material is declared effective.